Taẕkirah-yi muqat̤t̤aʻāt-i Urdū musammá banām-i tārīḵẖī Qit̤ʻah-yi muntaḵẖab - Nassāḵẖ, ʻAbdulg̲ẖafūr (Maulvi Alimuddin collection., 1874)
Selections from the works of Hindustani Poets, with short biographical notices.